School and future: failed interpellations - Southwell, Myriam Mónica (2017)
This article analyzes school / future articulation by dwelling on the ways in which it is currently enunciated in our schools, as well as on the evocation usually made of how that formulation worked in the not too distant past. It also proposes problematize whether this is the only way - with a universalist claim - that the school can be linked to the future or whether it is a particular story, and thus one of several possible ways.